ANALISIS ASOSIATIF PERILAKU MAKAN DAN TINGKAT KECUKUPAN GIZI PADA MAHASISWA UKM PENCAK SILAT UNESA ASSOCIATIVE ANALYSIS EATING WITH NUTRITIONAL ADEQUACY LEVEL OF STUDENT-ATHLETES PENCAK SILAT UNESA - Dina Restu Enggarsari (Poltekkes Kemenkes Surabaya, 2017)
Eating behavior is a way, perspective or action of someone towards food. Eating behavior of Pencak Silat students from FIK UNESA is different in each individual. It can be seen based on eating behavior, starts from eating out habit, food addict, dietary habit, and vegan dietary habit, athletes’ habit in consuming caffeine, soft drink, and fast food. If it is not taken care properly, it will affect nutritional adequacy level of Pencak Silat athletes. The general objective of this research is to analyze the relation between eating behavior (eating out habit, food addict, dietary habit, vegan dietary habit, athletes’ habit in consuming caffeine, soft drink, and fast food) and nutritional adequacy level of Pencak Silat athletes in FIK UNESA. This research was an analytic observational with cross sectional design. The data was obtained by using questionnaire to a sample of 33 students who are the members of UKM Pencak Silat UNESA. The result of this research showed that most of students are male (57,6%), most respondents aged 19 (33.3%), the majority of respondents have pocket money with the range of Rp. 500,000- Rp 1,200,000 (84,85%), most of them living in boarding house (45,5%) and have a knowledge of nutrition with the average score of 98.4, whereas according to the result by using spearman test from six eating behaviors related to nutritional adequacy level, it was obtained that dietary habit did not relate to nutritional adequacy level of respondents.Keywords: individual characteristics, eating behavior, nutritional adequacy level